2017
DOI: 10.1007/s11695-017-2838-8
|View full text |Cite
|
Sign up to set email alerts
|

Single Anastomosis Duodeno-Ileal Switch (SADIS): A Systematic Review of Efficacy and Safety

Abstract: As a modified bariatric procedure, SADIS has promising outcomes for weight loss and comorbidity resolution in morbidly obese patients. When measured, there was a high prevalence of macro-nutrient deficiencies following SADIS. There is a high technical variability, and long-term data are required before any meaningful conclusion can be made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(41 citation statements)
references
References 26 publications
3
33
0
2
Order By: Relevance
“…It is recognized that there is a growing interest in OAGB/MGB and SADIs and that, as yet, these are not covered robustly by clinical practice guidelines. Until such data emerge, it may be hypothesized that requirements for nutritional supplements in people undergoing OAGB/MGB with BP limb of 150 cm would be at least that of people undergoing RYGB, if not more, and that nutritional requirements for people undergoing OAGB/MGB with BP limb greater than 150 cm and SADIS would be at least that of people undergoing the traditional BPD/DS 163–166 . We therefore recommend that healthcare professionals follow RYGB nutritional recommendations for postoperative care after OAGB/MGB with BP limb length of 150 cm and BPD/DS recommendations for people after OAGB/MGB with BP limb length of greater than 150 cm or SADIs.…”
Section: Abnormal Test Results and Clinical Problemsmentioning
confidence: 99%
“…It is recognized that there is a growing interest in OAGB/MGB and SADIs and that, as yet, these are not covered robustly by clinical practice guidelines. Until such data emerge, it may be hypothesized that requirements for nutritional supplements in people undergoing OAGB/MGB with BP limb of 150 cm would be at least that of people undergoing RYGB, if not more, and that nutritional requirements for people undergoing OAGB/MGB with BP limb greater than 150 cm and SADIS would be at least that of people undergoing the traditional BPD/DS 163–166 . We therefore recommend that healthcare professionals follow RYGB nutritional recommendations for postoperative care after OAGB/MGB with BP limb length of 150 cm and BPD/DS recommendations for people after OAGB/MGB with BP limb length of greater than 150 cm or SADIs.…”
Section: Abnormal Test Results and Clinical Problemsmentioning
confidence: 99%
“…This weight regain could be reduced by diet modification, increasing the length of bypassed jejunum, or reducing the size of gastric pouch in intractable cases [30][31][32]. SADI-S procedure has been developed mainly to simplify the technique for biliopancreatic diversion (BPD) and many of the postoperative complications post-SADI-S procedure such as anastomotic leak or stricture were attributed to the learning curve and technical difficulties in the early phase of starting the SADI-S surgery as per previous studies [15,33]. We did not encounter such complications in our patients postoperatively or during follow-up; however, one of our patients developed intraabdominal collection postoperatively which was treated by aspiration and conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, selenium intake and markers of deficiency were most evident at 3 months after RYGB, but not LAGB, prompting recommendations for routine increases in high selenium foods and use of routine multivitamin supplements with more than 55 μg/d of selenium . In a more recent report, Shoar et al found about 50% of patients undergoing SADI‐S had a selenium deficiency.…”
Section: Executive Summarymentioning
confidence: 96%